Community and household well-being in the municipal corporation of Maharashtra - Mohanty, Sanjay K et al. (Urban India)
Increasing urbanisation and rising economic inequality are concomitant in India. Though studies have examined the level, pattern and trend of urbanization in Maharashtra, no attempt has been made to examine the level of well being across local bodies in urban India. Using data from the census of India 2011, this paper examines the variation in community and household well being in the municipal corporations of Maharashtra. Two composite indices of well being namely, community well beign index (CWI) and household well-being index (HWI) are used to depict the state of well being at the community and household levels respectively. Respectively. Results suggest large varations in HWI and CWI - Reproduced
Keywords: Urbanisation, Municipal corporation, Maharashtra, Well-being, India